Impact of COVID-19 public health safety measures on births in Scotland between March and May 2020. (January 2022) - Speyer, L.G.; Marryat, L.; Auyeung, B.
Abstract: Objective: To combat the widespread transmission of COVID-19, many countries, including the United Kingdom, have imposed nationwide lockdowns. Little is known about how these public health safety measures affect pregnant mothers and their offspring. This study aimed to explore the impact of COVID-19 public health safety measures on births in Scotland. Study design: Cross-sectional study. Methods: Using routinely collected health data on pregnancy and birth in Scotland, this study compares all births (N = 7342) between 24th March and May 2020 with births in the same period in 2018 (N = 8323) to investigate the potential negative impact of public health safety measures introduced in Scotland in spring 2020. Birth outcomes were compared using Mann-Whitney-U tests and chi-square tests. Results: Mothers giving birth during the pandemic tended to combine breastfeeding and formula-feeding rather than exclusively breastfeed or exclusively formula-feed, stayed in hospital for fewer days, and more often had an epidural or a spinal anaesthetic compared to women giving birth in 2018. Conclusion: Overall, results suggest little impact of public health safety measures on birth outcomes. Further research is needed to explore the longer-term impacts of being born in the pandemic on both maternal mental health and child development.